Effects of Low Protein Diet on Body Weight and Hematological Parameters in Rats - Zikrah, Azizah Amatu; Santoso, Putra; Maliza, Rita (Jurnal Biologi Tropis, 2024)
Malnutrition is a condition in which the body is deficient or excessive in macronutrients and micronutrients such as carbohydrates, fats, proteins and vitamins. Malnutrition causes changes in body weight and blood tissue that inhibit the development of hematopoietic cells, resulting in anemia, leukopenia and bone marrow hypoplasia. This study aimed to examine the effect of feeding a diet with a protein level of 12% and 20 % for 6-week to Wistar rats. The parameters seen are the impact on body weight and selected hematological parameters included white blood cell, monocyte, lymphocyte, granulocyte, hemoglobin and mean corpuscular volume. This study found that rats fed with 12% protein showed significant differences in body weight and several hematological parameters such as monocytes, lymphocytes, hemoglobin and mean corpuscular volume compared to normal.